Hubungan tingkat stres dengan gangguan siklus menstruasi mahasiswi Fakultas Kedokteran Universitas Palangka Raya - Karunia, Alda Jane; Balyas, Abi Bakring; Arifin, Syamsul; Kahanjak, Donna Novina; Widiarti, Astri (Barigas: Jurnal Riset Mahasiswa, 2024)
Stress is one of the factors causing menstrual cycle disorders in women. The highest level of stress is experienced by female students who are preparing a thesis as an undergraduate requirement. during the thesis writing process, they often face obstacles that have an impact on the menstrual cycle. This study aims to determine the relationship between stress levels and menstrual cycle disorders. This study used cross sectional study, chi square analysis technique with ρ value <0.05. The results of the study were 44 (56.4%) respondents had mild stress levels, 34 (43.6%) respondents had moderate stress levels, 54 (69.2%) respondents had normal menstrual cycles, 24 (30.8%) respondents had abnormal menstrual cycles. The results of bivariate analysis showed a relationship between stress levels and menstrual cycle disorders in female students of the Faculty of Medicine, University of Palangka Raya with chi square statistical test p-value = 0.046 (<0.05).